Nomination and Argumentation Strategies in Oratory Discourse: The Case of an English Sermon. (April 2017) - Mansouri, Sara; Biria, Reza; Mohammadi Najafabadi, Mohammad; Sattar Boroujeni, Susan
Inspired by critical discourse analysis and regarding language as a social medium whereby individuals, social groups, and institutions tend to express their beliefs and values, this study seeks to explore the persuasion and discourse strategies utilized in sermons. By focusing on the sermon of an influential native English orator and by employing Wodak's discourse–historical approach, it aims to investigate how the targeted religious genre unfolds to disclose the persuasive powers of the orator and its impact on the audience. The results obtained from the qualitative analysis of the corpus under investigation revealed that the speaker resorts to significant presentation of a wide range of topics to establish the oratory, and constructs the social actors through the application of nomination tools to qualify the selected actors through carefully formulated predication devices by laying out discursively logical justifications concerning various topos. Alternatively, the complementary quantitative corpus analysis using Corpus Presenter software also provided an insightful evidential basis reflecting orator's involvement, intensification of the intended illocutionary force, and his utilization of thought-provoking linguistic resources. Notably, the results presented here may shed light on the function of intertextuality in the genre of the sermon operationalized and activated through nomination strategies, the tools of argumentation theory, and interdiscursivity. Second, language learners' awareness of such elements may have an overriding importance in the process of text generation in speaking and writing processes.